Novel Therapeutic Potential of Mitogen-Activated Protein Kinase Activated Protein Kinase 2 (MK2) in Chronic Airway Inflammatory Disorders - Singh, Rakesh K.; Najmi, Abul Kalam (Current Drug Targets, 2019)
Objective: The primary focus of this review is to highlight the current and emerging proinflammatory role of MK2 kinase signaling in p38MAPK pathway and to provide a detailed evaluation on the prospects of MK2 inhibition with special emphasis on the etiology of chronic inflammatory airway diseases, such as asthma, idiopathic pulmonary fibrosis, lung cancer, acute lung injury and acute respiratory distress syndrome. Background: MK2 belongs to serine-threonine kinase family and is activated directly by stress and inflammatory signal through p38MAPK phosphorylation in diverse inflammatory conditions through the Toll-like receptor signaling pathway. MK2 has been thought to be a critical factor involved in the regulation of synthesis and release of pro-inflammatory (TNF-α, IL-6 and IL-1β, etc.) proteins. Targeted inhibition of MK2 kinase has been shown to significantly reduce the production and release of these cytokine molecules. Therefore, MK2 has been identified as an effective strategy (alternative to p38MAPK) to block this pro-inflammatory signaling pathway. Results: The inhibition of MK2 may lead to similar or better efficacy as that of p38 inhibitors, and interestingly avoids the systemic toxicity shown by the p38 inhibitors. Thus, MK2 has been the focus of intense interdisciplinary research and its specific inhibition can be a novel and potential therapeutic strategy for the treatment of chronic airway inflammatory diseases. Conclusion: Promising advancement in understanding and rigorous exploration of the role of MK2 kinase in inflammatory processes may contribute to the development of newer and safer therapy for the treatment of chronic airway inflammatory diseases in the future.
Keywords: chronic lung inflammation